Соотношение политического насилия и терпимости в современном обществе - Коровина, Д. (ХНУРЕ, 2022)
The article deals with the issues of correlation of political violence and political tolerance from the point of view of modern political science. It is shown that recently sound social tolerance has been undergoing changes and has become an artificially ideologized tolerance, “political correctness”, and wounded social groups have become its subjects. This situation contributes to the emergence of double standards, social lies and political violence. It is impossible to unambiguously interpret political violence, but all x definitions have something in common – it is coercion, oppression, lawlessness, abuse of power.
Keywords: терпимость в современном обществе